Sport, education and corporatisation spaces of connection, contestation and creativity - Kohe, Geoffery Z. 1983-; Collison, Holly (Routledge focus on sport, culture and society, 2019)
Using an interdisciplinary approach, Sport, Education and Corporatisation offers an important critique of the intersection between sport organisations, commercial agendas and educational development. It reveals a discomforting interplay between sector stakeholders that has been normalised via discourses of civic 'good', social responsibility and community welfare. The book employs stakeholder theory, corporate social responsibility ideals, and holistic constructions of space to provide a framework to understand some of the latent and explicit complexities of sport sector connectivity. Interrogating the key contexts, issues and challenges that emerge from the Sport-Education-Corporate nexus and drawing upon evidence from international, national and local sport organisations, it argues for sustained and rigorous examination of the commercialisation of educational agendas and new directions for education-based corporate social responsibility within the sport industry. This is an invaluable resource for researchers working in the areas of sport management; sport development; sociology of sport; sport policy and politics; physical education; and the wider economics, organisational politics and business ethics fields. It is also a fascinating read for students within sport business management, sports studies, sport politics and physical education programmes